Mesoscale dynamics in the Arabian Sea and a focus on the Great Whirl life cycle: A numerical investigation using ROMS. Issue 9 (22nd September 2014) - Vic, C.; Roullet, G.; Carton, X.; Capet, X.
Abstract The Great Whirl (GW) is a persistent anticyclonic mesoscale eddy that is observed seasonally in the Arabian Sea during a period embedding the 3 months of the southwest monsoon (June–July–August) at a quasi‐steady location. Its dynamics remain unclear despite it being one of the largest coherent vortices in the world ocean. Realistic regional numerical experiments using ROMS are performed to investigate the life cycle of the GW, which is not well resolved by sparse available in situ measurements in the region. Using a set of sensitivity experiments and an accurate temporal characterization of the eddy properties (including position, radius, depth, and vorticity) we (i) confirm the role of basin‐scale downwelling Rossby waves in the GW generation, (ii) clarify the role of the monsoonal strong anticyclonic wind in its maintenance and barotropization, and (iii) suggest a connection between basin‐scale Rossby wave dynamics and GW collapse.